PENGARUH PENERAPAN PENDEKATAN INKUIRI TERBIMBING MELALUI PROBLEM BASED LEARNING UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR SISWA SMPN 22 PADANG - Sufriyanti, Sufriyanti; ARDI, ARDI; Nerita, S.Pd, M.Pd, Siska (STKIP PGRI Sumbar, 2014)
ABSTRACT As part of natural sciences, biology has a significant role in the development of technology, which requires learning competence and comprehensive understanding. In reality, students tend memorize rather than understand. Based on observations, the subjects of biology was difficulty to understanding. Biology students understanding of the material is low-impact on student learning outcomes biology. Biology of learning strategies that are used are still teacher centered. The purpose of this study was to determine the effect of the application of quided inquiry approach through problem based learning (PBL) on the activity and learning out comes biology class VIII SMP 22Padang. This study was experimental design using randomized control group design. The study population was all students in class VIII SMP 22 Padang. Using random sampling techniques, and obtained VIII 5 class as well as the experimental class VIII 6 as control. Research instrument used is the achievement test. Data were analyzed using t-test. The results showed the average results of the experimental study on the class (71,98) is also higher than the learning activity in the control class (56,35). There fore it can be concluded that the application of quided inquiry learning through problem based learning (PBL) can enchance biologycal activity and learning out comes SMP 22 eighth garade students in padang.